A number synthesis method of the self-adapting upper-limb rehabilitation exoskeletons. (6th June 2017) - Li, Jianfeng; Zhang, Ziqiang; Tao, Chunjing; Ji, Run
The goal of this article is to present a number synthesis method for the self-adapting upper-limb rehabilitation exoskeletons. The human joint kinematics and the variability of joint axes around their supposed locations were analyzed; the axes misalignments caused by the wearing error and the movement coupling between joint rotations and axes motions in human joints were taken into account, and the kinematic incompatibility of upper-limb exoskeletons was investigated from an over-actuation perspective. Then, a number synthesis method of the self-adapting upper-limb exoskeletons was proposed by using the traditional degrees of freedom analysis approach of spatial multiloop chains. Applying this method, the basic chains of the self-adapting four-degrees of freedom shoulder–elbow and five-degrees of freedom shoulder–elbow–forearm exoskeletons were synthesized and classified into three and two groups, respectively. Finally, the feasible simplified chains of the self-adapting upper-limb exoskeletons were investigated with the consideration of the quasi-anthropopathic feature and structure simplicity, and several examples were enumerated. The proposed simplified chains could be used as the candidates for further studies on the performance analysis, the chain compare and selection, and structure design of the self-adapting upper-limb exoskeletons.